2023
DOI: 10.3390/cancers15041111
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Tumor Budding and Partial Epithelial–Mesenchymal Transition in Head and Neck Cancer

Abstract: Tumor budding (TB), a microscopic finding in the stroma ahead of the invasive fronts of tumors, has been well investigated and reported as a prognostic marker in head and neck squamous cell carcinoma (HNSCC). Epithelial–mesenchymal transition (EMT) is a crucial step in tumor progression and metastasis, and its status cannot be distinguished from TB. The current understanding of partial EMT (p-EMT), the so-called halfway step of EMT, focuses on the tumor microenvironment (TME). Although this evidence has been i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 122 publications
0
11
0
Order By: Relevance
“…Luo et al 45 reported that budding cells having fibroblast‐like phenotype were barely identifiable within cancer stroma; thus, they tackled the issue by staining the tumor sections with this cytosolic enzyme. The ALDH1 is a cancer stem cells marker that promotes the oxidation of proteins involved in the early stages of cell differentiation (aldehyde and retinoic acid) and they show that it resulted directly correlated with tumor aggressiveness 34,75 . To confirm the role of cancer cells stemness, in OSCC patients, the expression of CD44 resulted closely related to the EMT process and therefore to tumor aggressiveness 76 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Luo et al 45 reported that budding cells having fibroblast‐like phenotype were barely identifiable within cancer stroma; thus, they tackled the issue by staining the tumor sections with this cytosolic enzyme. The ALDH1 is a cancer stem cells marker that promotes the oxidation of proteins involved in the early stages of cell differentiation (aldehyde and retinoic acid) and they show that it resulted directly correlated with tumor aggressiveness 34,75 . To confirm the role of cancer cells stemness, in OSCC patients, the expression of CD44 resulted closely related to the EMT process and therefore to tumor aggressiveness 76 …”
Section: Discussionmentioning
confidence: 99%
“…The ALDH1 is a cancer stem cells marker that promotes the oxidation of proteins involved in the early stages of cell differentiation (aldehyde and retinoic acid) and they show that it resulted directly correlated with tumor aggressiveness. 34,75 To confirm the role of cancer cells stemness, in OSCC patients, the expression of CD44 resulted closely related to the EMT process and therefore to tumor aggressiveness. 76 In summary, budding cells show characteristics between EMT and cancer stem cells, such as morphology and lack of E-cadherin, high expression of β-catenin, vimentin, and matrix metalloproteinase.…”
Section: Biological Processes Associated With Tumor Budding In Hnsccmentioning
confidence: 99%
“…Of note, overexpression of factors involved in EMT has been associated with metastasis, advanced stages of disease and low overall survival rates in patients with various cancer types ( 76 , 77 ), and were confirmed in HNSCC ( 78 , 79 ). Okuyama et al ( 80 ) highlighted the association of tumor budding (defined as the presence of isolated clusters of up to five cancer cells ahead of the invasive tumor front) with p-EMT, and determined the potential of tumor budding as a prognostic marker for poor survival in HNSCC. Therefore, these biomarkers are potential targets for cancer treatment.…”
Section: Emtmentioning
confidence: 99%
“…EMT causes epithelial cells to acquire stemness, allowing them to convert into mesenchymal-like cells with improved motility, invasion, metastasis, and death resistance [ 47 , 66 , 70 , 80 ]. Autocrine stimulation of the transforming growth factor (TGF)-β signaling pathway leads to increased expression of EMT transcription factors such as twist-related protein 1 (TWIST1), zinc finger E-box-binding homeobox 1 (ZEB1), and Snail2 [ 47 , 70 , 81 ] ( Figure 4 A). TGF-β1 has also been linked to cancer cell invasion and to EMT in a variety of human cancers, and it is known to be regulated by ITGA6 [ 82 ].…”
Section: Itga6 As Biomarker Of Cancer Stem Cellsmentioning
confidence: 99%